Pathologic Fracture of the Mandible Secondary to Traumatic Bone Cyst. Issue 3 (September 2013) - Ahlers, Eric; Setabutr, Dhave; Garritano, Frank; Adil, Eelam; McGinn, Johnathan
The traumatic bone cyst (TBC) is an uncommon and poorly understood lesion. First described in 1929, TBCs lack an epithelial lining, typically occur during the second decade of life, and are most frequently located in the jaw. Although the majority of TBCs are asymptomatic, rarely a TBC can cause a pathologic fracture of the mandible. We present a case of an adolescent suffering a sports-related pathologic mandible fracture secondary to a traumatic bone cyst.